ANALYSIS OF STUDENTS' ENVIRONMENTAL LITERACY PROFILE ON BEHAVIORAL COMPONENTS IN CONSERVATION BIOLOGY LECTURES - Nisa Sholehah Pangsuma; Widi Purwianingsih; Mimin Nurjhani (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Environmental literacy can answer concerns about the problem of ecological crisis. The environmental literacy has a category of behavior. Behavior toward attitudes of ecological concern is shown in an individual's daily lifestyle and patterns. This study aims to analyze students' environmental literacy skills, especially in 6 components of attitude: energy conservation, mobility and transportation, waste avoidance, recycling, consumerism, and vicarious attitudes toward conservation. This is a survey study using a cross-sectional method. The research instrument is a questionnaire consisting of 40 positive and negative statements. The subjects of this study were biology education students who were taking conservation biology courses. The results show that students' environmental literacy is in a good category, that contains 74% overall have shown an attitude of environmental concern. Specifically, energy conservation has an excellent category (83%). This is indicated by the presence of 2 components of attitudes in the good category, which are waste avoidance (79%) and consumerism (79%). Meanwhile, the other 3 components show a sufficient category, especially vicarious behavior towards conservation (72%) the mobility and transportation component (66%), and waste recycling habits (65%). In conclusion, further habituation and education are needed to improve the pro-environmental behvaior, especially in the category that is still not good.